EFFECT OF ARTEMISIA SPLENDENS POWDER AND EXTRACT ON BROILER CHICKEN’S PERFORMANCE, LYMPHOID ORGAN WEIGHT, GUT MORPHOLOGY AND SERUM BIOCHEMICALS DURING COCCIDIOSIS CHALLENGE. - & Al-Barwary, Abdullah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The objective of this study was to investigate the efficacy of Artemisia splendens on performance, some serum biochemicals content, lymphoid organs and gut health of broiler chickens challenged with coccidia. This study was conducted at university of Duhok, college of agriculture. A total of 200 day-old Ross 308 chicks were assigned in to 5 treatments (4 replicates pens of 10 birds/pen): unchallenged control (negative control); challenged control (positive control); challenged supplemented with salinomycin in feed (anticoccidial); challenged supplemented with Artemisia splendens in drinking water (AS1) and challenged supplemented with Artemisia splendens in feed (AS2). On day 9, challenged birds were inoculated with 5000 sporulated oocysts of Eimeria. The results showed that on day 24, challenged birds in negative control, anticoccidial AS1 and AS2 had higher weight gain and feed conversion ratio compared to positive control. No significant differences were detected between Birds in AS1, AS2 Anticoccidial and negative control for body weight gain and feed conversion ratio. On day 35, birds in AS1 as negative control and anticoccidial groups had higher (P<0.01) body weight gain and feed conversion ration compared to positive control. Negative control, anticoccidial, AS1 and AS2 birds significantly increased villous height and villous height/crypt depth and decreased crept depth when compared to positive control at day 24. The serum globulin concentration of AS1 birds was significantly higher than birds in negative control, positive control and anticoccidial. In conclusion, these results demonstrated the protective effects of Artemisia splendens against performance during coccidiosis challenge.